Systematic Literature Review Adopsi Cloud Computing dalam Sistem Informasi Manajemen - Maulana Yusuf; Ines Heidiani Ikasari (Shofanah Media Berkah, 2023)
Cloud computing has emerged as a transformative technology in the field of Management Information Systems (MIS). It offers numerous benefits, such as cost savings, scalability, and flexibility, which have attracted organizations to adopt cloud computing solutions. This paper presents a systematic literature review (SLR) of cloud computing adoption in the context of MIS. The objective of this SLR is to provide an overview of the current state of research, identify key trends, and highlight research gaps in the adoption of cloud computing in MIS.